Indicators Of Nutritional Status Among MBBS Students in A Tertiary Care Centre, Indore - Madhuri Inamdar; Richa Nigam; Ashfaq Modiwala; Sonia Tiwari; Varsha Singh; Rajshekhar R Wavare (Medsci Publications, 2016)
Introduction- BMI can be used to estimate the prevalence of overweight and obesity within a population. It does not, however, account for the wide variations in obesity between different individuals and populations. BMI may not correspond to the same degree of fatness in different populations due to differences in body proportions. Material and Methods- This was a cross sectional study. The subjects were 232 pre final MBBS students. It was double stage cluster sampling. The students calculated BMI, waist circumference, Waist hip ratio and Calorie consumption of their own. Results- Mean Waist circumference (Male= 84.76, 7.646 SD; Female= 79.37, 9.343 SD) and waist hip ratio( male=0.880,0.055SD; Female=0.819, 0.067) were below cut off line. Calorie intake as per Indian standard was poor (Male=2098.5. 503.78SD; Female=1759.2, 362.90SD). Females were having increased risk and substantial increased risk of metabolic disorders as per waist circumference measurement (P>0.001, P>0.001). Males were more at risk as per waist hip ratio (P>0.001). At the BMI of pre-obese category, the female waist circumference was higher than cut off value (86.37 cm). Sensitivity found to be highest for waist hip ratio (28%). Conclusion- The WHR truly finding out the abdominal obesity.